Global biomes and ecozones – Conceptual and spatial communalities and discrepancies - Beierkuhnlein, Carl; Fischer, Jan-Christopher (ERDKUNDE, 2021)
Various facets of global changes and related problems and challenges are asking for sound impact assessments and corresponding coping strategies. The human impact on nature is a major driver of biodiversity loss and restricted ecosystem functioning and services. Assessing such global changes is often done by using biomes as benchmarks. However, even if the wording and terminology seem common sense (‘tropical rain forest’, ‘steppe’, ‘boreal forest’) global biome units and maps deviate in many ways. This is well justified by their individual intention, expert opinions, disciplinary background, and methodology of creation. A closer look reveals linkages between spatial accordance and common origin in climate classifications and maps. Their original influence, however, is rarely evident. In consequence, it is difficult if not impossible for users to realize and understand differences in these global maps. Furthermore, it is difficult to accept the fact that there is no common standard for global biomes. Even more surprising is the fact that some approaches are uncritically taken for common sense and are perpetuated over decades. This study aims to review established global biome concepts. Regions that are consistently assigned to comparable types of biomes shall be detected and also regions where ambiguity exists. For this purpose, we shortly review the history of existing concepts and the generic relations between them. Biomes, ecozones and climate classifications are considered. We digitized the most prominent biome classifications. Spatial match and mismatch between concepts were analyzed globally. We detect areas of spatial agreement and regions with ambiguous classifications. A clustering approach including 287 individual biomes originating from 12 established global biome concepts and their classifications/units revealed 12 terrestrial biome clusters among which 8 can be assigned to terrestrial ecological units. One cluster on ice caps adds to this. And finally, 3 clusters represent rather transition zones (ecotones), high mountain plateaus or are of minor areal extent. The spatial arrangement of these emerging clusters is displayed on a global map. Additionally, regions of uncertainty related to class assignment were identified. Those primarily occur in the vicinity of mountainous regions. The findings of this study should be seen as a work in progress and as a basis for further optimization of global biome concepts.